Plasmodium Reproduction, Cell Size, and Transcription: How to Cope With Increasing DNA Content? - Machado, Marta; Steinke, Salome; Ganter, Markus (Frontiers in Cellular and Infection Microbiology, 2021)
Plasmodium, the unicellular parasite that causes malaria, evolved a highly unusual mode of reproduction. During its complex life cycle, invasive or transmissive stages alternate with proliferating stages, where a single parasite can produce tens of thousands of progeny. In the clinically relevant blood stage of infection, the parasite replicates its genome up to thirty times and forms a multinucleated cell before daughter cells are assembled. Thus, within a single cell cycle, Plasmodium develops from a haploid to a polypoid cell, harboring multiple copies of its genome. Polyploidy creates several biological challenges, such as imbalances in genome output, and cells can respond to this by changing their size and/or alter the production of RNA species and protein to achieve expression homeostasis. However, the effects and possible adaptations of Plasmodium to the massively increasing DNA content are unknown. Here, we revisit and embed current Plasmodium literature in the context of polyploidy and propose potential mechanisms of the parasite to cope with the increasing gene dosage.